Mechanism of PDZK1 in Hepatocellular Carcinoma Complicated with Hyperuricemia. (14th November 2022) - Guo, Linqi; Jiang, Wenda; Quan, Lingli; Teng, Xinli; Zhao, Jing; Qiu, Hongbin
Abstract : Background . Hepatocellular carcinoma (HCC) is a kind of primary liver cancer that accounts for more than 90% of primary hepatocellular carcinomas. Hyperuricemia is closely related to the development, recurrence, metastasis, and prognosis of cancer. Previous studies have proved that the serum uric acid level can increase the incidence rate and mortality of malignant tumors. However, the specific pathogenesis remains unstudied. Methods . RT-qPCR analysis showed that the mRNA expression of PDZK1 and ABCG2 increased significantly after HCC cells were exposed to different concentrations of soluble uric acid (2.5, 5, 10, 20 mg/dl) for 24 hours. Then, in HCC shRNAs, PDZK1, or over expression PDZK1 were used. CCK8, wound healing, and Transwell assay showed that PDZK1 regulates cell proliferation, invasion, and migration. Flow cytometry results revealed that PDZK1 affects cell apoptosis. Western blot results show that PDZK1 affects the STAT3/C-myc pathway. Then, in vivo tumorigenesis, allopurinol maybe an effective drug to advance: the prognosis of HCC. Results . In our study, RT-qPCR analysis showed that the mRNA expression of PDZK1 and ABCG2 increased significantly after different concentrations of soluble uric acid in HCC. Then, PDZK1 affects the proliferation, migration, and apoptosis of HCC through the STAT3/C-myc pathway. Conclusions . Hyperuricemia response affects the expression of PDZK1; PDZK1 affects the proliferation, migration, and apoptosis through the STAT3/C-myc pathway in hepatocellular carcinoma. It is suggested that PDZK1 maybe closely related to the occurrence, development, and prognosis of HCC and allopurinol maybe have potential anticancer effects.